Arylimido‐Bridged Dinuclear Ti(μ‐NAr)2Ti Scaffold for Alkyne Insertion into the ortho‐C−H Bond of Arylimido Ligands. Issue 3 (25th November 2016) - Nagae, Haruki; Hato, Wataru; Kawakita, Kento; Tsurugi, Hayato; Mashima, Kazushi
Abstract: Dinuclear titanium dialkyl complexes bridged by two μ‐arylimido ligands, [CpTi(CH2 SiMe3 )(μ‐NAr)]2 (Cp=cyclopentadienyl) activated an ortho ‐aryl C−H bond of an μ‐arylimido ligand to form a four‐membered titanacycle. The subsequent insertion reaction of 1‐(trimethylsilyl)propyne into a metal–carbon bond of the four‐membered titanacycle yielded the corresponding six‐membered titanacycle. Further ortho ‐C−H bond activation of the other μ‐arylimido ligand and an insertion reaction proceeded to give dinuclear titanium complexes with two six‐membered titanacycles. An Eyring plot in the temperature range 130–150 °C revealed activation parameters for the alkenylation reaction, and deuterium‐labeling experiments showed that the C−H bond activation step is the rate determining step. Relative Gibbs free energies of the starting complexes, reaction intermediates, and transition states were calculated by using DFT calculations. Abstract : Building bridges : Imido‐bridged dinuclear titanium dialkyl complexes activated an ortho ‐C−H bond of a μ‐arylimido ligand to form a four‐membered titanacycle. A subsequent insertion reaction of an internal alkyne into a metal–carbon bond yielded a six‐membered titanacycle. Further ortho ‐C−H bond activation of the other μ‐arylimido ligand and an insertion reaction gave dinuclear titanium complexes with two six‐membered titanacycles (see figure). Kinetic and DFT studies clarify the reaction mechanism of the alkenylation reaction.